Copper-catalysed alkylation of heterocyclic acceptors with organometallic reagents - Guo, Yafei; Harutyunyan, Syuzanna R. (Beilstein Journal of Organic Chemistry, 2020)
Copper-catalysed asymmetric C–C bond-forming reactions using organometallic reagents have developed into a powerful tool for the synthesis of complex molecules with single or multiple stereogenic centres over the past decades. Among the various acceptors employed in such reactions, those with a heterocyclic core are of particular importance because of the frequent occurrence of heterocyclic scaffolds in the structures of chiral natural products and bioactive molecules. Hence, this review focuses on the progress made over the past 20 years for heterocyclic acceptors.
Keywords: conjugate addition; copper catalysis; heterocyclic Michael acceptor; organometallics

(untitled) - Harutyunyan, S. R.; den Hartog, T.; Geurts, K.; Minnaard, A. J.; Feringa, B. L. (Chem. Rev., 2008)

(untitled) - Alexakis, A.; Bäckvall, J. E.; Krause, N.; Pàmies, O.; Diéguez, M. (Chem. Rev., 2008)

(untitled) - Jerphagnon, T.; Pizzuti, M. G.; Minnaard, A. J.; Feringa, B. L. (Chem. Soc. Rev., 2009)

(untitled) - Schmid, T. E.; Drissi-Amraoui, S.; Crévisy, C.; Baslé, O.; Mauduit, M. (Beilstein J. Org. Chem., 2015)

(untitled) - Bates, R. W.; Sridhar, S. (J. Org. Chem., 2008)

(untitled) - Brown, M. K.; Hoveyda, A. H. (J. Am. Chem. Soc., 2008)

(untitled) - Chin, Y.-J.; Wang, S.-Y.; Loh, T.-P. (Org. Lett., 2009)

(untitled) - Pereira, C. L.; Chen, Y.-H.; McDonald, F. E. (J. Am. Chem. Soc., 2009)

(untitled) - Rani, R.; Granchi, C. (Eur. J. Med. Chem., 2015)

(untitled) - Vinogradov, M. G.; Turova, O. V.; Zlotin, S. G. (Org. Biomol. Chem., 2019)

(untitled) - Sharma, V.; Kumar, P.; Pathak, D. (J. Heterocycl. Chem., 2010)

(untitled) - Chung, Y. K.; Fu, G. C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Fustero, S.; Moscardó, J.; Jiménez, D.; Pérez-Carrión, M. D.; Sánchez-Roselló, M.; del Pozo, C. (Chem. – Eur. J., 2008)

(untitled) - Takahashi, K.; Midori, M.; Kawano, K.; Ishihara, J.; Hatakeyama, S. (Angew. Chem., Int. Ed., 2008)

(untitled) - Šebesta, R.; Pizzuti, M. G.; Boersma, A. J.; Minnaard, A. J.; Feringa, B. L. (Chem. Commun., 2005)

(untitled) - Endo, K.; Ogawa, M.; Shibata, T. (Angew. Chem., Int. Ed., 2010)

(untitled) - Pizzuti, M. G.; Minnaard, A. J.; Feringa, B. L. (Org. Biomol. Chem., 2008)

(untitled) - Guo, Y.; Harutyunyan, S. R. (Angew. Chem., Int. Ed., 2019)

(untitled) - Müller, D.; Alexakis, A. (Org. Lett., 2012)

(untitled) - Fernández-Ibáñez, M. Á.; Maciá, B.; Pizzuti, M. G.; Minnaard, A. J.; Feringa, B. L. (Angew. Chem., Int. Ed., 2009)

(untitled) - Alexakis, A.; Amiot, F. (Tetrahedron: Asymmetry, 2002)

(untitled) - Rideau, E.; You, H.; Sidera, M.; Claridge, T. D. W.; Fletcher, S. P. (J. Am. Chem. Soc., 2017)

(untitled) - Gao, Z.; Fletcher, S. P. (Chem. Sci., 2017)

(untitled) - Schäfer, P.; Sidera, M.; Palacin, T.; Fletcher, S. P. (Chem. Commun., 2017)

(untitled) - Ardkhean, R.; Roth, P. M. C.; Maksymowicz, R. M.; Curran, A.; Peng, Q.; Paton, R. S.; Fletcher, S. P. (ACS Catal., 2017)

(untitled) - Wang, J. Y. J.; Palacin, T.; Fletcher, S. P. (Org. Lett., 2019)

(untitled) - Némethová, I.; Bilka, S.; Šebesta, R. (J. Organomet. Chem., 2018)

(untitled) - Vila, C.; Hornillos, V.; Fañanás-Mastral, M.; Feringa, B. L. (Chem. Commun., 2013)

(untitled) - Teichert, J. F.; Feringa, B. L. (Chem. Commun., 2011)

(untitled) - Pineschi, M.; Del Moro, F.; Gini, F.; Minnaard, A. J.; Feringa, B. L. (Chem. Commun., 2004)

(untitled) - Rodríguez-Fernández, M.; Yan, X.; Collados, J. F.; White, P. B.; Harutyunyan, S. R. (J. Am. Chem. Soc., 2017)

(untitled) - Cottet, P.; Müller, D.; Alexakis, A. (Org. Lett., 2013)

(untitled) - Liang, L.; Su, L.; Li, X.; Chan, A. S. C. (Tetrahedron Lett., 2003)

(untitled) - Tian, M.; Pang, Z.-b.; Li, H.-f.; Wang, L.-l. (Tetrahedron: Asymmetry, 2017)

(untitled) - Yan, M.; Zhou, Z.-Y.; Chan, A. S. C. (Chem. Commun., 2000)

(untitled) - Brown, M. K.; Degrado, S. J.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2005)

(untitled) - Clavier, H.; Coutable, L.; Toupet, L.; Guillemin, J.-C.; Mauduit, M. (J. Organomet. Chem., 2005)

(untitled) - Mao, B.; Fañanás-Mastral, M.; Feringa, B. L. (Org. Lett., 2013)

(untitled) - Rideau, E.; Fletcher, S. P. (Beilstein J. Org. Chem., 2015)

(untitled) - Jacques, R.; Pullin, R. D. C.; Fletcher, S. P. (Nat. Commun., 2019)

(untitled) - Ladjel, C.; Fuchs, N.; Zhao, J.; Bernardinelli, G.; Alexakis, A. (Eur. J. Org. Chem., 2009)

(untitled) - Bos, P. H.; Rudolph, A.; Perez, M.; Fañanás-Mastral, M.; Harutyunyan, S. R.; Feringa, B. L. (Chem. Commun., 2012)

(untitled) - Palais, L.; Bournaud, C.; Micouin, L.; Alexakis, A. (Chem. – Eur. J., 2010)

(untitled) - Jumde, R. P.; Lanza, F.; Veenstra, M. J.; Harutyunyan, S. R. (Science, 2016)

(untitled) - Lanza, F.; Pérez, J. M.; Jumde, R. P.; Harutyunyan, S. R. (Synthesis, 2019)

(untitled) - Jumde, R. P.; Lanza, F.; Pellegrini, T.; Harutyunyan, S. R. (Nat. Commun., 2017)

(untitled) - Fillion, E.; Wilsily, A. (J. Am. Chem. Soc., 2006)

(untitled) - Dumas, A. M.; Fillion, E. (Acc. Chem. Res., 2010)

(untitled) - Wilsily, A.; Fillion, E. (J. Org. Chem., 2009)

(untitled) - Wilsily, A.; Fillion, E. (Org. Lett., 2008)

(untitled) - Fillion, E.; Wilsily, A.; Liao, E.-T. (Tetrahedron: Asymmetry, 2006)

(untitled) - Wilsily, A.; Lou, T.; Fillion, E. (Synthesis, 2009)